Pengaruh Variasi Tekanan Terhadap Kerapatan, Kadar Air Dan Laju Pembakaran Pada Biobriket Limbah Kayu Mahoni - Aditiya Darma Rinanda; Wahidin Nuriana; Sutrisno Sutrisno (LPPM Universitas Merdeka Madiun, 2021)
Abstractâ€” The use of biomass from mahogany wood waste briquettes as a substitute fuel for oil and gas requires briquette technology. Mahogany wood briquette is able to convert into fuel with a fairly good conversion efficiency, high density and ease of storage and distribution. The purpose of this study was to determine the effect of pressure variations on the density, moisture content and rate of burning of mahogany wood waste briquettes. The process of making charcoal biobriquettes begins with the carbonization process with a temperature of 400 ÌŠC, then smoothed and sieved with a size of 80 mesh - 100 to get the same size, and using tapioca adhesive 30% of the weight of the mixture. The mixture is put into a molding machine and then printed with a pressure of 80 kg/cm2, 115 kg/cm2, 150 kg/cm2, and 185 kg/cm2. Charcoal biobriquettes are dried in an oven at 105 ÌŠC for 1 hour. In this research, the mass density and moisture content of the mahogany wood waste met the Indonesian biobriquette standards, the results of this study obtained the higher density of 0,55 g/cm3at a pressure of 150 kg/cm2. The results lowest water content of 47,2% at a pressure of 185 kg/cm2. The lowest combustion rate is 0,257 g/min at a pressure of 185 kg/cm2.Â Keywordsâ€”: mahoni wood waste; pressure; moisture content; combustion rate.